2019
DOI: 10.1002/da.22982
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pharmacotherapies for smoking cessation in anxiety disorders: Subgroup analysis of the randomized, active‐ and placebo‐controlled EAGLES trial

Abstract: Background Smoking rates are high in adults with anxiety disorders (ADs), yet little is known about the safety and efficacy of smoking‐cessation pharmacotherapies in this group. Methods Post hoc analyses in 712 smokers with AD (posttraumatic stress disorder [PTSD], n = 192; generalized anxiety disorder [GAD], n = 243; panic disorder [PD], n = 277) and in a nonpsychiatric cohort (NPC; n = 4,028). Participants were randomly assigned to varenicline, bupropion, nicotine‐replacement therapy (NRT), or placebo plus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
6
0
4
Order By: Relevance
“…Of those with PTSD who received varenicline, there were no statistically significant differences in CAR from Week 9 to Week 12 vs placebo. 5 However, there was a significant difference in individuals with GAD (OR 4.53; 95% CI, 1.20 to 17.10), and panic disorder (OR 8.49; 95% CI, 1.57 to 45.78). 5 In contrast to CAR from Week 9 to Week 12, 7-day point prevalence abstinence at Week 12 for participants with PTSD was significant (OR 4.04; 95% CI, 1.39 to 11.74) when comparing varenicline to placebo.…”
Section: Further Analysis Of Eaglesmentioning
confidence: 91%
See 3 more Smart Citations
“…Of those with PTSD who received varenicline, there were no statistically significant differences in CAR from Week 9 to Week 12 vs placebo. 5 However, there was a significant difference in individuals with GAD (OR 4.53; 95% CI, 1.20 to 17.10), and panic disorder (OR 8.49; 95% CI, 1.57 to 45.78). 5 In contrast to CAR from Week 9 to Week 12, 7-day point prevalence abstinence at Week 12 for participants with PTSD was significant (OR 4.04; 95% CI, 1.39 to 11.74) when comparing varenicline to placebo.…”
Section: Further Analysis Of Eaglesmentioning
confidence: 91%
“…5 However, there was a significant difference in individuals with GAD (OR 4.53; 95% CI, 1.20 to 17.10), and panic disorder (OR 8.49; 95% CI, 1.57 to 45.78). 5 In contrast to CAR from Week 9 to Week 12, 7-day point prevalence abstinence at Week 12 for participants with PTSD was significant (OR 4.04; 95% CI, 1.39 to 11.74) when comparing varenicline to placebo. Within the anxiety disorder cohort, there were no significant differences in moderate to severe NPSAE rates based on treatment group.…”
Section: Further Analysis Of Eaglesmentioning
confidence: 91%
See 2 more Smart Citations
“…Patients with schizophrenia smoke more cigarettes, take more frequent puffs over a shorter duration, extract more nicotine from a cigarette, suffer greater withdrawal and are more dependent on nicotine than those without mental illness. 6 , 9 , 22 , 41 Ayers et al 42 found that patients with anxiety disorders were more likely to suffer neuropsychiatric adverse events during smoking cessation than those without. Du Plooy et al 9 found that 87.8% of male smokers in a South African psychiatric hospital smoked daily.…”
Section: The Relationship Between Smoking and Mental Illnessmentioning
confidence: 99%